Dendritic Cell Targeting Effectively Boosts T Cell Responses Elicited by an HIV Multiepitope DNA Vaccine - Apostólico, Juliana de Souza; Lunardelli, Victória Alves Santos; Yamamoto, Marcio Massao; Souza, Higo Fernando Santos; Cunha-Neto, Edecio; Boscardin, Silvia Beatriz; Rosa, Daniela Santoro (Frontiers in Immunology, 2017)
Despite several efforts in the last decades, an efficacious HIV-1 vaccine is still not available. Different approaches have been evaluated, such as recombinant proteins, viral vectors, DNA vaccines and, most recently, dendritic cell (DC) targeting. This strategy is based on DC features that place them as central for induction of immunity. Targeting is accomplished by the use of chimeric monoclonal antibodies directed to DC surface receptors fused to the antigen of interest. In this work, we targeted eight promiscuous HIV-derived CD4+ T cell epitopes (HIVBr8) to the DEC205+ DCs by fusing the multiepitope immunogen to the heavy chain of αDEC205 (αDEC205HIVBr8), in the presence of the TLR3 agonist poly (I:C). In addition, we tested a DNA vaccine encoding the same epitopes using homologous or heterologous prime-boost regimens. Our results showed that mice immunized with αDEC205-HIVBr8 presented higher CD4+ and CD8+ T cell responses when compared to mice that received the DNA vaccine (pVAXHIVBr8). In addition, pVAX-HIVBr8 priming followed by αDEC205HIVBr8 boosting induced higher polyfunctional proliferative and cytokine producing T cell responses to HIV-1 peptides than homologous DNA immunization or heterologous αDEC prime/DNA boost. Based on these results, we conclude that homologous prime-boost and heterologous boosting immunization strategies targeting CD4+ epitopes to DCs are effective to improve HIV-specific cellular immune responses when compared to standalone DNA immunization. Moreover, our results indicate that antigen targeting to DC is an efficient strategy to boost immunity against a multiepitope imunogen, especially in the context of DNA vaccination.